Hubungan Teoritis Antara Berat Isi Kering dan Kadar Air untuk Menentukan Kepadatan Relatif - Syafruddin Syafruddin (INFO-TEKNIK, 2007)
Soil stabilization can be done with a few way, by increasing soil density or compaction. Compactable soil can increase soil strength and bearing capacity to working payload.Laterite soils as embankment soil that stabilized with compacting method, influenced by water content, dry unit weight and compacting dissociation energy. To know theoretical connection between water contents,  dry unit weight, degree of saturation  and energy of compaction is done in laboratory with method Standard Proctor and Modified Proctor to know optimum water content zone at some Sr and determines minimum energy that needed to gets relative density of 90% ( RC 90%) so that economic compacting can be reached.From result of this research, it is gotten that optimum water content resided at Sr 75% and there is no compacting curve cuts Sr 100% ( ZAV).By using theoretical connection between dry unit weight , water content, Sr and compacting energy, it can determine the water content zone and minimum energy that needed to reachs relative density of 90% ( RC 90%).